Vermiculita como substrato para o teste de germinação de sementes de ipê-amarelo - Martins, Cibele Chalita [UNESP]; Machado, Carla Gomes; de Santana, Denise Garcia; Zucareli, Claudemir (Universidade Estadual de Londrina (UEL), 2012)
Vermiculite is a substrate used in seedling production of forest species and can be an option for the germination test of ipe seeds. The objective of this research was to evaluate the use of vermiculite in the germination test of Tabebuia chrysotricha seeds and to stablish appropriate particle size and moisture for this substrate. Four replications of 20 seeds were sown in soil, sand, paper rolls, and vermiculite with different particle sizes: micron (0.15-0.20 mm), superthin (0.21-0.30 mm), thin (0.30-0.50 mm) and medium (0.50-1.19 mm) moistened with water equivalent to 0.5, 1.0, 1.5 and 2.0 times the weight of the dry subtrate. Germination test was carried out at 30 degrees C. The percentage of normal seedlings was obtained seven days after sowing (first count) and then weekly until 28 days, when abnormal seedlings and dead seeds were also counted. It was concluded that the germination test of ipe seeds can be carried out with thin or medium vermiculite moistened with water equivalent to 1.5 times the dry weight of the substrate. These treatments resulted in higher and faster germination (21 days).
Vermiculite as substrate for germination test of ipe seeds
Keywords: Moistening; speed of germination; Vigor; Tabebuia chrysotricha